Board diversity and intellectual capital performance - Al-Musali, Mahfoudh Abdul Karem Mahfoudh; Ku Ismail, Ku Nor Izah (Emerald Group Publishing Limited, 2015)
Purpose– The purpose of this paper is to investigate if the effectiveness of board meetings moderates the relationship between board diversity (in terms of educational level and nationality) and intellectual capital (IC) performance. Design/methodology/approach– The empirical data are drawn from banks’ annual reports over the three-year period of 2008 to 2010. Public’s value-added intellectual coefficient method is applied to measure IC performance. The frequency of board meetings is used a proxy for board meeting effectiveness.Findings– Based on the hierarchical regression analysis, our results do not support the hypothesis that the effect of board diversity on IC performance is positive as the effectiveness of board meetings increases.Practical implications – Findings of this study indicate that there is a need for more effective meetings through providing appropriate and sufficient information to directors, particularly in strategic issues such as those related to IC that could make board members better prepared and more involved in meetings.Originality/value– This study adds to the literature, as it is the first study that explores the variables that could affect the relationship between board diversity and IC performance in the context of banks.